Caracterização da Situação Epidemiológica das Leishmanioses na Colômbia, 2007 – 2016 - Elena Maria Hurtado (2020)
According to the World Health Organization, neglected tropical zoonoses include leishmaniasis, diseases of worldwide distribution. Two forms of presentation are described, American Tegumentary Leishmaniasis (ATL) and Visceral Leishmaniasis (VL). In the Americas, leishmaniasis is present in 18 countries, and Colombia is among the 10 countries with the highest number of cases of Cutaneous Leishmaniasis (CL) in the world and for VL, among those with the highest case records. In order to know the epidemiological situation of leishmaniasis in Colombia from 2007 to 2016, a descriptive ecological study of morbidity and mortality by leishmaniasis was conducted considering the reported cases obtained from the National Public Health Surveillance System - SIVIGILA. Spatial, temporal and sociodemographic aspects were analyzed and characterized for both leishmaniasis. Over 10 years, 103.943 cases of leishmaniasis were reported. Of these, 99,74% of ATL, with 17 deaths and 0,25% of VL with 5 deaths. The largest percentage of the population suffering from ATL in Colombia was between 21 and 50 years old, male, black, mulatto or Afro-Colombian, living in rural areas, where the Central region was responsible for the largest number of reported cases per annum. The highest incidence of ATL occurred in 2009, with 34.28 cases per 100.000 inhabitants. For VL, there was a higher frequency in males, under five years old, indigenous and rural residents, with the Caribbean region being the most noteworthy throughout the study period, with the highest incidence observed in 2007 with 0,118 cases per 100.000 inhabitants. Epidemiological patterns of leishmaniasis in Colombia have shown variations in morbidity and mortality in recent years with greater population involvement by ATL. The present study contributed to improve the understanding of this important public health problem and to direct surveillance and control actions specific to the regions with higher incidence in the country.